The Art of the Consult Call: Improving Communication Through Shared Mental Models - Monica Saladik; Michelle Noelck; Jessica Bailey (Association of American Medical Colleges, 2023)
Introduction The Accreditation Council for Graduate Medical Education cites effective communication with physicians as a core competency for emergency medicine (EM) residents. However, there is no standardized curriculum dedicated to communication beyond practice in the clinical setting. Methods We developed a 1-hour EM didactic session on effective consultations using experiential education principles. Learners were placed in pairs of one junior learner and one senior learner. The junior learner performed a mock phone consultation using an EM patient case; the senior learner completed an online evaluation, assessing the junior learner on 13 core components of a successful consult call, based on Kessler's 5Cs consultation model. Subsequently, learners participated in an intervention, which included an artistic activity and facilitated debrief, connecting their reflections to clinical practice. Postintervention, the same paired learners completed a second mock consultation call and reevaluation. Finally, learners completed a feedback survey. Results Fifteen pairs completed both the pre- and postintervention evaluations. Of the junior learners simulating the consultation call, 47% were clinical medical students, and 53% were first-year EM residents. Preintervention, learners completed a mean of 51% of core consult call components compared to a mean of 84% postintervention. This 33% improvement was statistically significant (p < .001; 95% CI, 19.9-46.1). Eight participants completed the feedback survey; 100% agreed or strongly agreed with positive statements regarding overall session content. Discussion This engaging interactive session utilizing a mock communication exercise, unique artistic activity, and guided reflection can effectively increase junior learners' phone consultation communication skills.